Kinetic patterns of liver enzyme elevation with COVID-19 in the USA. Issue 11 (November 2020) - Da, Ben L.; Mitchell, Robert A.; Lee, Brian T.; Perumalswami, Ponni; Im, Gene Y.; Agarwal, Ritu; Schiano, Thomas D.; Dieterich, Douglas; Saberi, Behnam
Abstract : COVID-19 is a global pandemic that started in Wuhan, China. COVID-19 related liver enzyme elevations have been described however the clinical presentation, enzyme kinetics, and associated laboratory abnormalities of these patients have not been well described. Five cases of COVID-19 associated liver enzyme elevations are reported here. We found that COVID-19 related liver enzyme elevations occurred in a hepatocellular pattern and persisted throughout the initial hospitalization in all patients. Abnormalities in lactate dehydrogenase and ferritin levels were seen in all five cases. In conclusion, abnormalities in aminotransferase, lactate dehydrogenase, and ferritin levels are commonly seen in COVID-19 related liver injury. Elevated aminotransferase levels often persist throughout the entire hospitalization. However, the clinical course of COVID-19 related liver injury appears benign.